The psychology of women and gender : half the human experience + - Else-Quest, Nicole; Hyde, Janet Shibley (Thousand Oaks Sage, 2018)
"With clear, comprehensive, and cutting-edge coverage Psychology of Women and Gender delivers an authoritative analysis of classical and up-to-the-minute research from a feminist, psychological viewpoint. The text thoroughly examines the balance of cultural and biological similarities (and differences) between the genders, noting how these characteristics may affect issues of equality as well as how men and women behave toward one another. Reflecting cutting edge developments from the field, the text puts research into context and clearly explains the relationship between gender and emotion--helping to demystify the scientific process and study of feminist psychology. It includes expansive ethnicity coverage, hands-on applications, and case studies that give students further experience with key issues. This proven text equips students with a strong foundation for understanding the influences of gender, race, and ethnicity on psychology and society, as well as strategies for thinking critically about pop culture versus academic feminism as it relates to psychology"--
"Our textbook Half the human experience: the psychology of women had a good run, through eight editions. But then ... many things changed ... In light of these major shifts, we decided that the field needed not a new edition, but a very new book ... We developed a new title that pays homage to the textbook from which it was derived ..."--Preface.
Earlier editions published as: Half the human experience : the psychology of women [by] Janet Shibley Hyde, Nicole Else-Quest.
Includes bibliographical references (pages 415-492) and index.
Keywords: Women -- Psychology; Sex differences